Linkage isomerism of (diamine)platinum(II) complexes of sulfur-containing ylidenemalonate ligands - Kim, KM; Jun, MJ; Sohn, YS (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
A H-1 NMR study has-been carried out on (diamine)platinum(II) complexes of 1,3-dithian-2- ylidenemalonate (DTAYM) and 1,3-dithiepane-2-ylidenemalonate (DTEYM) ligands as anionic leaving group in aqueous solution. Only the O,S-chelated isomer was observed in solution for all the DTAYM complexes regardless of the kind of carrier ligand amine as was in the solid state. However, both O,S-and S,S'-chelated isomers were observed in solution for DTEYM complexes, which show linkage isomerism from the O,S-chelate to the thermodynamically more stable S,S'-chelate. The rate of linkage isomerism of the DTEYM complexes was found to be dependent on their amine co-ligands. Molecular dynamics of the DTAYM complexes was also discussed based on their temperature-dependent NMR spectra. The crystal structure of the S,S'-isomer of (NH3),Pt(DTEYM). H2O was determined whereas that of the O,S-isomer could not be obtained due to its poor crystallinity. (C) 1997 Elsevier Science Ltd.
Keywords: NUCLEAR MAGNETIC-RESONANCE; CIS-DIAMMINEDIAQUAPLATINUM(II) CATION; PLATINUM COMPLEXES; ANTITUMOR-ACTIVITY; RING REVERSAL; AMINO-ACIDS; GLUTATHIONE; CISPLATIN; METHIONINE; REACTIVITY